2018
DOI: 10.1108/978-1-78756-793-1-00044
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Stress Level and Degree of Depression in the Elderly at a Nursing Home in Lhokseumawe in the Year 2017

Abstract: Purpose-The objective of this research is to know the correlation of stress level with the degree of depression in the elderly at a nursing home in Lhokseumawe in the year 2017. Design/Methodology/Approach-This research is analytic using a cross-sectional approach with a total sampling method. The total number of samples was 55 respondents. Findings-The results showed that the elderly in a Lhokseumawe nursing home at average are at mild stress level to medium degree of depression. Pearson correlation test resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Indeed, prior studies said that stress had a significant positive correlation with depression (r=0.406, p=0.002), with more than 20-fold higher risk for having depressive symptoms (OR: 20.84, p<0.001) among individuals with increased stress levels. 48,49 Life stress was also significantly associated with depression, even among healthy individuals (z=3.01, p=0.003). 50 It had been shown that there is a link between stress and depression.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, prior studies said that stress had a significant positive correlation with depression (r=0.406, p=0.002), with more than 20-fold higher risk for having depressive symptoms (OR: 20.84, p<0.001) among individuals with increased stress levels. 48,49 Life stress was also significantly associated with depression, even among healthy individuals (z=3.01, p=0.003). 50 It had been shown that there is a link between stress and depression.…”
Section: Discussionmentioning
confidence: 98%
“…Previous Polish studies have sounded the alarm that single factors of mental disorders: stress and fear have a negative impact on teachers' health and the effectiveness of their work (Grzegorzewska, 2018). Considering the frequent co-occurrence and amplification of these factors (Domagalska et al, 2021;Yuziani & Maulina, 2018), the mental health problem in this group is even greater.…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa penelitian menunjukkan bahwa stres pada lansia berdampak pada kualitas tidur, kondisi kesehatan, depresi dan kualitas hidup. Faktor yang paling berkontribusi terhadap kejadian tersebut adalah aktivitas sehari-hari, dukungan sosial, persepsi terhadap status kesehatan, tingkat pendidikan, gangguan kesehatan kronik dan masalah ekonomi [6][7][8][9][10][11] . Putu N (2020) berpendapat bahwa tingkat stres dan kualitas tidur memiliki hubungan yang positif yang berarti semankin tinggi tingkat stres pada lansia semakin buruk kualitas tidurnya.…”
unclassified